Assessment and Optimization of Clean Energy Equity Risks and Commodity Price Volatility Indexes : Implications for Sustainability - Dutta, Anupam; Bouri, Elie; Das, Debojyoti; Roubaud, David (Elsevier, 2020)
Although clean energy equities have emerged as a new asset class for market participants, especially environmentally concerned investors, existing and previous studies pay very little attention to how equity investors in clean energy markets can reduce their downside risk. The authors of this paper address this void by considering the roles of the commodity market volatility indexes of crude oil, gold and silver. Using the dynamic conditional correlation model, the results show that commodity volatilities and clean energy equity prices move in opposite directions. Based on the hedging effectiveness, each of the three volatility indexes performs as an effective tool for reducing the risk of clean energy equity indexes. Meanwhile, the implied volatility index of crude oil is the most effective tool, followed by that of gold and silver. The application of an asymmetric model confirms the main findings. The findings extend the limited understanding on how to hedge the downside risk of clean energy stock indices, and provide useful implications to market participants on the ability of implied volatility indexes of major commodities to hedge that risk.
Keywords: Clean energy equities; Commodity market volatility; Time-varying correlations; Hedging effectiveness; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|